The Clinical Impact and Cost Implications of Endoscopic Ultrasound on the Use of Endoscopic Retrograde Cholangiopancreatography in a Canadian University Hospital - Nassir Alhayaf; Eoin Lalor; Vincent Bain; John McKaigney; Gurpal Singh Sandha (Canadian Journal of Gastroenterology)
BACKGROUND: Endoscopic ultrasound (EUS) is a safe alternative to endoscopic retrograde cholangiopancreatography (ERCP) for diagnostic biliary imaging in choledocholithiasis. Evidence linking a decline in diagnostic ERCP with the introduction of EUS in clinical practice is limited.